Wastewater Treatment and Reuse in the Food Industry - Barbera, Marcella (Chemistry of Foods,, 2018)
This Brief is devoted to clean drinking water, which is (one of) the most important asset(s) in the food and beverage industry. In the present time of increasing water scarcity in many areas of the world, supply of clean water especially in the production and packaging chain of foods and beverages, is a crucial issue. This Brief hence outlines why functioning purification and reuse systems for wastewater are becoming more and more interesting and promising technologies in solving the challenge. Readers find in this Brief an introduction to different innovative treatment methodologies. The authors discuss key parameters (such as the water volume to be treated, types and chemical and physico-chemical characteristics of pollutants, but also the intended use of the recycled water) and present various methodologies, such as separation or concentration systems, centrifugation, evaporation, filtration, flotation, gravity separation, membrane techniques, aerobic and anaerobic biological treatments, as well as combined or hybrid systems. Selected specific methods are presented in detail, specifically a new adsorption method for the removal of metal ions.